ANALISIS PERHITUNGAN PENYETORAN PELAPORAN DAN PENCATATAN PPH PASAL 21 DAN PPN PT X - CHRISTYE NOVELLA; TJHAI FUNG NJIT (Jurnal Bisnis dan Akuntansi, 2017)
There are three objectives in this study. The first objective is to analyze the procedures for calculation, payment, reporting and recording of the income tax article 21 and value added tax (VAT) in PT X. The second objective is to analyze the implementation mechanism of calculation, payment, reporting and recording of the income tax article 21 and VAT in accordance with the PER-32/PJ/2015 and Law VAT No. 42 in 2009. The third objective is to analyze the recording of income tax article 21 and VAT in accordance to general tax accounting principle. The data used in this research is secondary data, which are SPT Future income tax article 21 and VAT, VAT invoices, tax payment slip income tax and VAT, reported evidence of income tax arcticle 21 and VAT. The method used in this research is a descriptive analysis of Income Tax Article 21 and VAT for analyzing the calculation, payment, reporting and recording of Income Tax Article 21 and VAT at the PT X, the implementastion accordance to the PER-32/PJ/2015 and Law VAT No. 42 in 2009 and generally accepted tax accounting principle. Based on the analysis, the results of the research showed overall income tax article 21 and VAT are in accordance with the PER-32/PJ/2015 and Law AT No. 42 Year 2009 as well as generally accepted accounting principles of taxation. However, there is an error in recording the salaries and rectification Tax Article 21 as a whole carried out during 2015.